PENGUKURAN KINERJA PERUSAHAAN PENYEDIA JASA KEUANGAN DENGAN MENGGUNAKAN PENDEKATAN BALANCED SCORECARD (Studi Kasus Pada PT. BPRS Artha Pamenang) - ISMAYANTIKA DYAH PUSPASARI; AYU EVIANA (Jurnal Akademika, 2015)
The purpose of this study was to measure how the performance of PT. BPRS ArthaPamenang in 2015 as measured by the method of balance scorecard. This research isdescriptive quantitative research with a sample of 30 respondents 30 respondents employeesand customers. The method of analysis used validity and reliability. Results from this studyis that the performance of the financial perspective PT. BPRS Artha Pamenang in 2015 isquite good, the performance of the customer's perspective is good, from the point of view ofinternal business process perspective is considered good, the performance of learning andgrowth perspective is quite good. It can be concluded that the performance of PT. BPRSArtha Pamenang for 2015 is good.Keywords: performance measurement, balance scorecard.